Partial Purification of Alkaline Protease as Thrombolytic Agent from Mutant Strain Bacillus licheniformis EMS250-O-1 - Zaman, Md Asad uz; Mamun, Md Arafat Al; Khan, Shakila Nargis; Hoq, Md Mozammel; Mazid, Md Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2017)
Thrombosis leads to myocardial infarction, stroke and other cardiovascular complications. Microbial thrombolytic agents such as urokinase, streptokinase etc. are used to treat complications related to thrombosis. To search for new microbial enzymes as thrombolytics having better efficacy and specificity, Bacillus licheniformis EMS-O-1 mutant strain was cultured in modified urea-molasses media followed by purification using ammonium sulphate precipitation and ultrafiltration through centricon tube of 100 MWCO value. The yield of crude enzyme was 11129.14 U/mg and after purification 40180.46 U/mg. Purification process increased the specific activity of purified enzyme to 12.28 fold with a recovery of 17.79%. The purified enzyme was a serine protease with molecular weight of 25.5 kDa as confirmed by irreversible inhibition of activity with phenylmethylsulfonyl fluoride (PMSF) followed by SDS-PAGE gel image and by LC-MS analyses. In vitro clot lysis assay of the purified enzyme exhibited 38.30% thrombolytic activity. The crude enzymes from the mutant strain EMS-O-1 were found to be stable up to 50oC and showed maximum stability between pH range 7.5 to 8.5. These findings signify that proteases produced by B. licheniformis mutant have the potential to be developed as a viable thrombolytic agent. Dhaka Univ. J. Pharm. Sci. 15(2): 135-141, 2016 (December)